Epoetin alfa drug use evaluation using a software system: lessons learned. - Armstrong E; Cherrick R (Disease Management & Health Outcomes, 2000)
Objective: To assess the utility of using a computer software program to determine whether epoetin alfa therapy drug use evaluation (DUE) criteria were met. Study design: Computer software was designed to allow pharmacists to enter patient data such as haematocrit results and iron stores into a database. DUE data were collected upon entry into the study (through medical record review), at 6 months and at 12 months after enrollment for both the treatment and control groups (see Interventions section). The analyses of the 6- and 12-month DUE process and outcome criteria were conducted through an automated algorithm that was part of the software. The DUE evaluation was collected as part of a randomised, prospective, controlled study conducted at 32 sites across the US. Interventions: At least 1 pharmacist at each study site completed a 4-day training session on end-stage renal disease and haemodialysis treatment, principles of anaemia management, use of an epoetin alfa software program, and review of specific DUE criteria. The treatment group consisted of patients managed by a trained pharmacist working in collaboration with a nephrologist being responsible for monitoring, evaluating and recommending epoetin alfa dosage regimens for patients. The control group consisted of patients for whom pharmacists monitored and collected haematocrit data but did not recommend therapy to the nephrologists. Main outcome measures and results: There were no statistically significant differences between patients in both the treatment and control groups with regard to the DUE results. However, the study demonstrated that computer databases can assist in determining whether specific DUE criteria have been met at multiple patient care sites. The computer software applied the same consistent methodology across a broad range of hospital practice sites and thus may have minimised investigator bias or site to site variations in criteria application. Conclusions: Future DUE software algorithms should allow investigators/pharmacists to adjust important parameters such as the criterion threshold, time period of monitoring, ability to code 'excused' gaps in data and flexibility to modify criterion parameters.